Glacio-Fluvial Landform Analysis of Upper Pinder River Basin, Central Himalaya - Prasad, Naresh; Joshi, R C (National Geographical Journal of India, 2022)
Pindar River originates from Pindari glacier trending from N-Wto S-E direction. The present study is an attempt to understand the development of landforms in the upper Pinder river basin. In the selected area prominent glaciers are Pindari (4150 m.), Kaphani (4459 m.) and Sundardhunga (4400 m.). Morphological features caused by glacial action are very important to interpret paleo climate processes. Snow line is retreating rapidly as a result glacial and glacio uvial actions are found important for land form development in the area. On the basis of altitude, dissection pattern, landform and process the study area is divided into three geomorphic units, e.g. glaciated, depositional and uvial area. 'U' shaped valleys, hanging valleys, arêtes, crevasses, horns, troughs, ice elds, and moraines are main glacial landforms in the area. Prominent glacio-uvial landforms are outwash plain, alluvial Fan, debris ow etc. 'V' shaped valley, gorge, waterfall, rapid and river terrace. Some gravity inuenced landforms i.e. talus/scree deposits, and fans are also observed in the study area. The length of Pindari glacier is about 6.4 km and retreating rapidly. Total recession of Pindari glacier during 1854 to 1906 was 1600 m while, in 1906-1958 it retreated 1054 m. From 1958 to 2010 it retreated 440 m. Clast analysis based on the eld investigation indicates various size, shape, fabric and surface features.